Duration of the Presence of Infectious Zika Virus in Semen and Serum. (27th July 2018) - Medina, Freddy A; Torres, Giselle; Acevedo, Jenny; Fonseca, Sharon; Casiano, Leslie; De León-Rodríguez, Carlos M; Santiago, Gilberto A; Doyle, Katherine; Sharp, Tyler M; Alvarado, Luisa I; Paz-Bailey, Gabriela; Muñoz-Jordán, Jorge L
Abstract: Zika virus (ZIKV) has recently caused a large epidemic in the Americas that is associated with birth defects. Although ZIKV is primarily transmitted by Aedes mosquitoes, ZIKV RNA is detectable in blood and semen of infected individuals for weeks or months, during which sexual and other modes of transmission are possible. However, viral RNA is usually detectable longer than infectious virus is present. We determined the frequency of isolation of infectious virus from semen and serum samples prospectively obtained from a cohort of patients in Puerto Rico. We confirmed isolation of infectious virus on the basis of a tissue culture cytopathic effect, an increase in virus genome copy equivalents (GCE), and positive results of immunofluorescence analysis; virus in infected cells was quantitated by flow cytometry. These criteria confirmed the presence of infectious virus in semen specimens from 8 of 97 patients for up to 38 days after initial detection when virus loads are >1.4 × 10 6 genome copy equivalents/mL. Two serum isolates were obtained from 296 patients. These findings can help guide important prevention guidelines for persons that may potentially be infectious and transmit ZIKV sexually. Abstract : We determined the frequency of isolation of infectious Zika virus from semen and serum samples prospectively obtained from a cohort of patients. Infectious Zika virus was found in semen up to 38 days after onset of symptoms.